The Correlation Study: Parental Attention and Learning Motivation of Students With Intellectual Disabilities - Rezky Ultabaini; Grahita Kusumastuti (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the relationship between parental attention and learning motivation of mentally retarded students. This study uses quantitative methods with the type of correlation research. The population in this study were six children with mental retardation at the SMALB level. Saturated sampling technique or total sampling where all the population is sampled. The data collection technique used a questionnaire technique using the parental attention instrument which contained seven aspects with 22 items while on learning motivation there were six aspects with 17 statement items. The collected data is then searched for data analysis using simple linear regression analysis techniques. The results of the data analysis of this study indicate that there is a significant positive relationship between parental attention and learning motivation of mentally retarded children in the high category.